Implementasi Undang-Undang Pornografi dan Undang-Undang Transaksi dan Informasi Elektronik terhadap Konten Bermuatan Ketelanjangan sebagai Kebebasan Berekspresi di Media Sosial - Fauzi, Mhd. Abyan (Universitas Serang Raya, 2023)
In the context of people's rights, posting nudity-containing content on social media is frequently linked to freedom of expression. Instead, Indonesia upholds moral principles, ethics, decency, and noble conduct at all times to preserve human dignity. This study looks at how electronic information and transaction regulations, as well as laws against pornography, are being applied to social media content that contains nudity. By adopting a normative and sociological legal approach to a variety of literary works as well as laws and regulations, this study uses the library research method. The findings of this study demonstrate that posting nudity-containing material on social media is, in theory, a banned act under the law. However, the lack of specific guidelines for nudity standards and penalties has consequences for many uploads of nudity-containing content on social media, which is readily accessible by anyone, anywhere, at any time. In order to create a helpful environment free of pornography, this study urges the public authority to create regulations controlling and managing the use of the internet and social media.